2013
DOI: 10.1371/journal.pone.0070514
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Acid Phosphatase (SapM) of Mycobacterium tuberculosis Is Indispensable for Arresting Phagosomal Maturation and Growth of the Pathogen in Guinea Pig Tissues

Abstract: Tuberculosis (TB) is responsible for nearly 1.4 million deaths globally every year and continues to remain a serious threat to human health. The problem is further complicated by the growing incidence of multidrug-resistant TB (MDR-TB) and extensively drug-resistant TB (XDR-TB), emphasizing the need for the development of new drugs against this disease. Phagosomal maturation arrest is an important strategy employed by Mycobacterium tuberculosis to evade the host immune system. Secretory acid phosphatase (SapM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 42 publications
3
71
0
1
Order By: Relevance
“…The DKO mutant was also found to be susceptible to oxidants, indicating towards a role of SapM in repressing the oxidative burst as seen for acid phosphatases from other intracellular pathogens [19][20][21]. Similar results using MtbDsapM mutant were obtained by Puri et al [26]. The study was taken a step further and conducted in an animal model and guinea pigs infected with MtbDsapM were shown to have an enhanced survival in comparison to Mtb infected animals.…”
Section: Sapmmentioning
confidence: 58%
See 2 more Smart Citations
“…The DKO mutant was also found to be susceptible to oxidants, indicating towards a role of SapM in repressing the oxidative burst as seen for acid phosphatases from other intracellular pathogens [19][20][21]. Similar results using MtbDsapM mutant were obtained by Puri et al [26]. The study was taken a step further and conducted in an animal model and guinea pigs infected with MtbDsapM were shown to have an enhanced survival in comparison to Mtb infected animals.…”
Section: Sapmmentioning
confidence: 58%
“…This study implicated that Mtb SapM would somehow block the activation and recruitment of DCs thus helping the bacteria lower down the severity of adaptive immune response. The studies which followed [25,26] however, unequivocally indicated toward a role of Mtb SapM in phagosome maturation arrest thereby substantiating the results obtained by Vergne et al [22]. In an attempt to create Mtb derived vaccine strain with a potential to undergo phagosome lysosome fusion, Saikolappan et al [25] generated a double knock out (DKO) strain, by deleting the genes fbpA and sapM in Mtb (DfbpADsapM).…”
Section: Sapmmentioning
confidence: 74%
See 1 more Smart Citation
“…SapM is a secretory phosphatase that dephosphorylates phosphatidylinositol 3-phosphate (PI3P) on the phagosome membrane [87]. PI3P is essential for phagosomes to acquire lysosomal constituents; it is involved in the docking of rab effector proteins early endosomal autoantigen 1 (EEA1) and hepatocyte growth factor-regulated tyrosine kinase (HRS) substrate, which are important for phagosome maturation [89]. Disruption of sapM in MTB resulted in a highly attenuated strain with an impaired ability to grow in the THP-1 macrophages as well as in the guinea pig tissues [33].…”
Section: Phagosome Arrestingmentioning
confidence: 99%
“…Such maturation arrest of phagosomes containing Mycobacterium tuberculosis is thought due to defective recruitment of rab proteins in such phagosomes [11]. Mycobacterial factor like secreted acid phosphatase is also thought to be important for inhibition of phagolysosome biogenesis [12]. As a result the tuberculosis bacterium resides inside the phagosome without experiencing the adverse environment produced by lysosomal acid hydrolases.…”
Section: Phagosomal Niche For Mycobacterium Tuberculosismentioning
confidence: 99%